(untitled) (Applied Biological Research, 2017)
The present study was aimed to screen ruminants for the prevalence of antibodies against four major persistent production-limiting infections in different agro-climatic zones of West Bengal (India). Two-hundred and twenty (n = 220) serum samples from cattle (n = 74), goats (n = 109) and sheep (n = 37) were collected from four agro-climatic zones of West Bengal. In present study, IBR antibodies was detected in 11 sera samples (11/74, 14.8%) collected from cattle only. Antibodies against BVD was detected in sera samples collected from three sheep (3/37, 8.1%) and one cattle (1/74, 1.3%). The MAP antibodies were detected in sera samples collected from three goats (3/109, 2.7%), two sheep (2/37, 5.4%) and one cattle (1/74, 1.3%). The antibodies against Chlamydophila abortus was confirmed in sera samples collected from two cattle (2/74, 2.6%). The study revealed lower seroprevalence of four major persistent and production limiting microbial infection in ruminants in Bengal.